The Other Futurism : Futurist Activity in Venice, Padua, and Verona - Bohn, Willard, 1939- (Book collections on Project MUSE., 2004)
Their provocative manifestos and outrageous performances earned the Italian Futurists international fame but, surprisingly, very little recognition outside of Italy for their actual achievements. The few English and American critics who have studied the movement in any depth have focused on the first phase, which spanned the years 1909-15 and was centred in Milan, Rome, and Florence. By contrast, the second phase covered a much longer period and represented a pan-Italian phenomenon. Despite the wealth of material available about this later part of the movement, there has been little attempt to survey Futurist activity outside of the major geographical centres in any detail or to relate it to the Futurist mainstream. In The Other Futurism, Willard Bohn seeks to remedy this oversight by examining the work of Futurists in Venice, Padua, and Verona from 1909 to 1944. He considers these local artists and writers both in terms of their relationship with F.T. Marinetti, who remained the major theorist and organizer of Futurist activities, and of their own specific adaptations and appropriations of Futurist theory. Conceived as a combination literary history and critical study, The Other Futurism looks at particular examples of literature, visual arts, and the performing arts and, using a series of rare documents, sheds new light on the complex cultural and political issues at the heart of this neglected chapter in Italy's history.